Discrimination training affects stimulus generalization in mice during Pavlovian eyeblink conditioning - Fiocchi, Francesca Romana; van Dorp, Nikki E. S.; Dijkhuizen, Stephanie; van den Berg, Maurits; Wong, Aaron; De Zeeuw, Chris I.; Boele, Henk-Jan (Frontiers in Behavioral Neuroscience, 2024)
The delicate balance between discrimination and generalization of responses is crucial for survival in our ever-changing environment. In particular, it is important to understand how stimulus discrimination affects the level of stimulus generalization. For example, when we use non-differential training for Pavlovian eyeblink conditioning to investigate generalization of cerebellar-related eyelid motor responses, we find generalization effects on amount, amplitude and timing of the conditioned responses. However, it is unknown what the generalization effects are following differential training. We trained mice to close their eyelids to a 10kHz tone with an air-puff as the reinforcing stimulus (CS+), while alternatingly exposing them to a tone frequency of either 4kHz, 9kHz or 9.5kHz without the air-puff (CS-) during the training blocks. We tested the generalization effects during the expression of the responses after the training period with tones ranging from 2kHz to 20kHz. Our results show that the level of generalization tended to positively correlate with the difference between the CS+ and the CS- training stimuli. These effects of generalization were found for the probability, amplitude but not for the timing of the conditioned eyelid responses. These data indicate the specificity of the generalization effects following differential versus non-differential training, highlighting the relevance of discrimination learning for stimulus generalization.